2017
DOI: 10.1103/physrevb.95.214416
|View full text |Cite
|
Sign up to set email alerts
|

Detection of induced paramagnetic moments in Pt onY3Fe5O12via x-ray magnetic circular dichroism

Abstract: Magnetic moments in an ultra-thin Pt film on a ferrimagnetic insulator Y3Fe5O12 (YIG) have been investigated at high magnetic fields and low temperatures by means of X-ray magnetic circular dichroism (XMCD). We observed an XMCD signal due to the magnetic moments in a Pt film at the Pt L3-and L2-edges. By means of the element-specific magnetometry, we found that the XMCD signal at the Pt L3-edge gradually increases with increasing the magnetic field even when the field is much greater than the saturation field … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 73 publications
0
15
1
Order By: Relevance
“…This is because, if the proximity-induced Pt ferromagnetism exists in these systems, the ISHE voltage induced by the spin-current phenomena may be contaminated by the anisotropic magnetoresistance or anomalous Nernst effect due to the magnetized Pt [3,4,8,21,[21][22][23][24][25][26][27][28]. Hence, the separation of the spincurrent contribution from magnetic-proximity-effect contribution is important in spintronics, and the detection of Pt ferromagnetism in the Pt/magnetic-oxide systems has attracted much attention [29][30][31][32][33][34][35][36][37][38]. Recent studies demonstrated that, in Pt/Y 3 Fe 5 O 12 , Pt/NiFe 2 O 4 , Pt/CoFe 2 O 4 , and Pt/Fe 3 O 4 , the proximity-induced parasitic contribution is negligibly small in comparison with the spin-current contribution to SMR or SSE [4, 8, 15, 17, 24-27, 29, 31-35, 39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because, if the proximity-induced Pt ferromagnetism exists in these systems, the ISHE voltage induced by the spin-current phenomena may be contaminated by the anisotropic magnetoresistance or anomalous Nernst effect due to the magnetized Pt [3,4,8,21,[21][22][23][24][25][26][27][28]. Hence, the separation of the spincurrent contribution from magnetic-proximity-effect contribution is important in spintronics, and the detection of Pt ferromagnetism in the Pt/magnetic-oxide systems has attracted much attention [29][30][31][32][33][34][35][36][37][38]. Recent studies demonstrated that, in Pt/Y 3 Fe 5 O 12 , Pt/NiFe 2 O 4 , Pt/CoFe 2 O 4 , and Pt/Fe 3 O 4 , the proximity-induced parasitic contribution is negligibly small in comparison with the spin-current contribution to SMR or SSE [4, 8, 15, 17, 24-27, 29, 31-35, 39].…”
Section: Introductionmentioning
confidence: 99%
“…Since the end of 1990s, a number of XMCD and XRMR studies focusing on Pt/3d-ferromagnetic-metal (Fe, Ni, Co, and Ni 81 Fe 19 ) junction systems have been reported and the Pt ferromagnetism in these systems has been established [44][45][46][47][48][49][50][51][52][53][54][55][56]. Recently, these techniques were applied for the Pt/magnetic-oxide systems: Pt/Y 3 Fe 5 O 12 [29][30][31]36], Pt/NiFe 2 O 4 [32,33,37], Pt/CoFe 2 O 4 [34,35,37], Pt/MnFe 2 O 4 [37], and Pt/Fe 3 O 4 [37]; in contrast to the Pt/3d-ferromagnetic-metal systems, the proximity-induced Pt ferromagnetism in these Pt/magnetic-oxide systems was found to be undetectably small when the effect of Pt oxidization is negligible [30,31]. These results suggest that small magnetization of the magnetic oxides is disadvantageous to inducing proximity ferromagnetism in the adjacent Pt layer; Y 3 Fe 5 O 12 , NiFe 2 O 4 , CoFe 2 O 4 , and Fe 3 O 4 are insulators or highly-resistive conductors [57][58][59] and their volume magnetization is much smaller than that of the 3d-ferromagnetic-metals [60].…”
Section: Introductionmentioning
confidence: 99%
“…Such behavior is not observed for a Pt film in contact with a nonmagnetic substrate, Gd 3 Gd 5 O 12 (GGG). Besides, the Pt/YIG system exhibits an unconventional Hall effect, whose magnetic-field dependence scales like a Brillouin function (not the magnetization curve of YIG) under high magnetic fields [9,10]. The feature is totally different from the normal Hall effect for Pt with a non-magnet (GGG) contact [10].…”
Section: Introductionmentioning
confidence: 94%
“…Note that this result supports the proposed origin of the anomalous Hall effect. That is, metallic Fe can act as a paramagnetic impurity in the Pt layer, giving rise to a skew scattering for itinerant electrons in Pt [10].…”
Section: Correct Figmentioning
confidence: 99%
See 1 more Smart Citation